Analysis of the effects of amyloid-β on astrocytes - González-Reyes, Rodrigo Esteban (Trinity College (Dublin, Ireland). Department of Physiology, 2011)
Alzheimer’s disease (AD) is a neurodegenerative pathology characterized by the presence of extracellular plaques composed of amyloid-β (Aβ) protein and intracellular neurofibrillary tangles composed of tau protein. Aβ, in particular Aβ1-42, has been shown to be neurotoxic and to induce functional and morphological changes in astrocytes and microglia. Despite the extensive research in AD, the precise cellular and molecular alterations associated with the development of the disease are unknown. The aims of this study were to determine, in vivo, the effects chronic intracerebroventricular (icv) treatment with Aβ has in the brains of aged and young Wistar rats and to explore age-related changes, and, in vitro, to examine the effects Aβ treatment has on cytokine production and release and to investigate the signalling pathways and membrane receptors involved in this process, in rat isolated astrocytes. The data showed that icv treatment with Aβ induced the appearance of immunoreactive structures accompanied by an increase in the astrocytic marker GFAP, and a decrease in the microglial marker CD 11b in the brains of aged, but not young rats; no changes were observed in other markers of microglial activation, spatial learning or in pro-inflammatory cytokines.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin